The Investigation of Undergraduate EFL Learners’ Viewpoints on Employing Tiktok as a Medium in Learning Speaking and Listening Skills - Setiawan, Budi; Yusuf, Aiman Syahrizal; Deviyanto, Deviyanto; Hamzani, Khairul; Agustina, Yulia (Universitas PGRI Adi Buana Surabaya, 2024)
This research aims to explore the perception of English language education students at Universitas Hamzanwadi regarding the utilization of TikTok as a tool for improving the speaking and listening skills. This study employed quantitative survey-based approach with 165 participants from the second to eighth semester. To collect the data, the researcher distributed Google Form which containing a total of 21 statements: ten assertions focused on students’ speaking skills and eleven statements focused on their listening skills. each statement was design to gauge students’ perceptions of TikTok as a tool for enhancing these language skills. The participants responded the statements by the Likert scale; strongly agree, agree, disagree, and strongly disagree. The data analysis involved calculating the frequency and percentage of responses for each statement to determine overall trends in perceptions. The findings reveal that students perceive TikTok as an engaging platform for enhancing speaking skills, facilitating pronunciation and intonation learning, boosting confidence, motivating regular practice, expanding vocabulary, exposing them to various accents, and aiding fluency development. Moreover, TikTok was seen as beneficial for improving listening skills, particularly in understanding different accents, comprehending content at various speeds, offering diverse and engaging content, motivating practice, and enhancing overall listening proficiency. TikTok has shown potential as a valuable supplementary tool for language learning; however, its integration into formal educational settings requires further investigation. It may be beneficial to explore specific strategies for incorporating TikTok into curricula, such as using it for vocabulary building, cultural exposure, or student-generated content to enhance engagement.